The effects of emotions on football spectators’ satisfaction and behavioural intentions - Biscaia, Rui (2012)
The goal of this study was to examine the relationship between spectators’ emotions, satisfaction, and behavioural intentions at football games. A survey was conducted among spectators of the top Portuguese professional football league during eight games (n 466). The sport emotion questionnaire was used to assess spectators’ emotions and the results gathered from a structural equation model suggest that analysis of specific emotions is crucial to understand spectators’ responses. Findings provide evidence that only the emotion of joy has a positive direct effect on satisfaction, as well as an indirect effect on behavioural intentions, via satisfaction. In turn, dejection has a negative direct effect on behavioural intentions, while satisfaction positively influences behavioural intentions. These results suggest managerial implications, such as the need to improve stadium atmosphere and social facilitation in order to provide an enjoyable overall experience to the spectators, and contribute to overall spectator satisfaction and positive behavioural intentions.